Low Serum LH Levels During Ovarian Stimulation With GnRH Antagonist Protocol Decrease the Live Birth Rate After Fresh Embryo Transfers but Have No Impact in Freeze-All Cycles - Luo, Yiyang; Liu, Shan; Su, Hui; Hua, Lin; Ren, Haiying; Liu, Minghui; Wan, Yuting; Li, Huanhuan; Li, Yuan (Frontiers in Endocrinology, 2021)
Objective: To explore the association between serum LH levels and the cumulative live birth rate (CLBR) within one complete cycle, and the impact of serum LH levels on the live birth rate (LBR) after the initial embryo transfer (ET) considering different ET strategies (fresh or freeze-all). Design: A retrospective cohort study. Setting: University-affiliated reproductive center. Patients: 1480 normogonadotrophic women who underwent COS with GnRH antagonist protocol for the first IVF/ICSI attempt. Intervention(s): The sample was stratified into low and higher LH groups according to serum LH peak levels of <4 (Group A) and ≥4 IU/L (Group B) during COS. Patients were also sub-grouped into fresh transfer and freeze-all cycles. Main outcome measure(s): The LBR after the initial embryo transfer and the CLBR within one complete cycle. Secondary outcome measure(s): The numbers of day-3 high-quality embryos, the numbers of embryos available, and the other pregnancy outcomes after the initial ET. Result(s): In comparison with the higher LH group, the CLBRs decreased significantly in the low (63.1% vs. 68.3%, P =.034) LH group. Subgroup analysis revealed that patients with low LH levels had lower LBRs after fresh embryo transfers (38.0% vs. 51.5%, P=.004) but comparable LBRs after the first FETs in freeze-all cycles (49.8% vs. 51.8%, P=.517) than patients with higher LH peak levels. Following confounder adjustment, multivariable regression analyses showed that low LH level was an independent risk factor for the CLBR (odds ratio (OR): 0.756, 95% confidence interval (CI): 0.604-0.965, P=.014). Moreover, the adverse impact of low LH levels on LBRs maintained statistically significant after fresh transfers (OR: 0.532, 95% CI: 0.353-0.800, P=.002) but not after the first frozen-thawed ETs in freeze-all cycles (OR: 0.918, 95% CI: 0.711-1.183, P=.508). Conclusion(s): In comparison with higher LH levels, low LH levels decrease the CLBRs per oocyte retrieval cycle for normogonadotrophic women who underwent COS using GnRH antagonists. This discrepancy may arise due to the significant detrimental effect of low LH levels on the LBRs after fresh embryo transfers.